Water resource characterization in canal command area for Jhansi minor (left bank canal of Bargi dam) of Rani Avanti Bai Sagar irrigation project- A case study - MISHRA, C. D.; TIWARI, Y. K.; NEMA, A. K.; NEMA, R. K.; SINGH, GAURAV; KUMAR, RAJESH (Journal of Soil and Water Conservation, 2020)
The present study was conducted on Jhansi minor of left bank canal network of Rani Avanti Bai Sagar irrigation project. This paper presents the characterization of command area based on water resource utilisation assessment with conjunctive use of surface and ground water, distribution of tube wells and lift irrigation pumps with reference to cropping pattern in study area. The results indicated that the middle reach of Jhansi minors is larger than its head and tail. The gravity irrigation was maximum during 2001-02 and then continuously decreased within last 10 years however tube well and pumped irrigated area has continuously increased. Cropping pattern also changed after introduction of different irrigation methods with different sources of irrigation. The wheat and chickpea were major crops grown in the area. The un-irrigated wheat, chickpea and pea were replaced by irrigated wheat, chickpea and pea. The water available from canal and tube well to command area was 1.71 Mm3 and 0.85 Mm3 respectively. The total number of tube wells in command area was 46. The use of canal water was higher in its head reach than tail and middle reach during initial years but during recent years conjunctive use of canal and ground water was observed in all the reaches of the command area.